2002
DOI: 10.1016/s0092-8674(02)01045-0
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C-γ Is Required for Agonist-Induced Ca2+ Entry

Abstract: We report here that PLC-gamma isoforms are required for agonist-induced Ca2+ entry (ACE). Overexpressed wild-type PLC-gamma1 or a lipase-inactive mutant PLC-gamma1 each augmented ACE in PC12 cells, while a deletion mutant lacking the region containing the SH3 domain of PLC-gamma1 was ineffective. RNA interference to deplete either PLC-gamma1 or PLC-gamma2 in PC12 and A7r5 cells inhibited ACE. In DT40 B lymphocytes expressing only PLC-gamma2, overexpressed muscarinic M5 receptors (M5R) activated ACE. Using DT40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
187
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(199 citation statements)
references
References 59 publications
9
187
3
Order By: Relevance
“…Activation of the lipase activity of PLC c2 leads to an increase in the IP 3 concentration, leading subsequently to an increase in the Ca 2+ concentration (Berridge 1993;Carpenter and Ji 1999;Patterson et al 2002;Nishida et al 2003). However, the treatment of PC12 cells with forskolin increases the intracellular concentration of cAMP but not Ca 2+ (data not shown), suggesting that PLCc2 mediates the phosphorylation of CREB in a Ca 2+ -independent manner following the activation of the cAMP signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Activation of the lipase activity of PLC c2 leads to an increase in the IP 3 concentration, leading subsequently to an increase in the Ca 2+ concentration (Berridge 1993;Carpenter and Ji 1999;Patterson et al 2002;Nishida et al 2003). However, the treatment of PC12 cells with forskolin increases the intracellular concentration of cAMP but not Ca 2+ (data not shown), suggesting that PLCc2 mediates the phosphorylation of CREB in a Ca 2+ -independent manner following the activation of the cAMP signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, siPLCc2 completely abolished the activation of CREB induced by treatment of cells with ionomycin, indicating that PLCc2 is essential for the activation of CREB by Ca 2+ signaling in PC12 cells. A previous report has demonstrated that PLCc2 amplifies the Ca 2+ signaling (Patterson et al 2002;Nishida et al 2003). Additionally, numerous studies have indicated that an increase in the intracellular Ca 2+ concentration leads to activation of CaMKs and PKCs (Nishizuka 1988;Schulman et al 1992;Hook and Means 2001;Elgersma et al 2004;Griffith 2004).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations